2008
DOI: 10.1016/j.neuroscience.2007.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent secretion of neuronal activity regulated pentraxin from vasopressin neurons into the systemic circulation

Abstract: Neuronal activity regulated pentraxin (Narp) is a secreted, synaptic protein that has been implicated in modulating synaptic transmission. However, it is unclear how Narp secretion is regulated. Since we noted prominent Narp immunostaining in vasopressin neurons of the hypothalamus and in the posterior pituitary, we assessed whether it, like vasopressin, is released into the systemic circulation in an activity-dependent fashion. Consistent with this hypothesis, electron microscopic studies of the posterior pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…This pattern of Narp localization in axons and terminals is also consistent with previous studies that have demonstrated that Narp, which is a secreted protein, is trafficked down axons to terminals in other pathways, e.g. mossy fibers of dentate granule cells (Reti et al, 2002b) and to vasopressin terminals in the posterior pituitary (Reti et al, 2008a). Moreover, electron microscopy studies have also shown that vasopressin (Reti et al, 2008a) and orexin (I.M.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This pattern of Narp localization in axons and terminals is also consistent with previous studies that have demonstrated that Narp, which is a secreted protein, is trafficked down axons to terminals in other pathways, e.g. mossy fibers of dentate granule cells (Reti et al, 2002b) and to vasopressin terminals in the posterior pituitary (Reti et al, 2008a). Moreover, electron microscopy studies have also shown that vasopressin (Reti et al, 2008a) and orexin (I.M.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in the hippocampus, Narp is selectively expressed in dentate granule cells (Reti et al, 2002b). In the hypothalamus, Narp is only expressed in a small population of neurons, including orexin and vasopressin neurons (Reti et al, 2002c and 2008a). We also observed Narp terminal staining in the dorsal horn of the spinal cord which was markedly reduced by dorsal rhizotomy, suggesting Narp is trafficked to the dorsal horn from DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Narp is a recognized intermediate-early gene product induced by hyperactivity in vivo (24,55,99). Here, we show that Narp mRNA expression is dramatically induced together with VGLUT2 after a prolonged increase in endogenous glutamatergic synaptic activation of neocortical neuronal networks in vitro.…”
Section: E-t Coupling Via Camentioning
confidence: 66%